Factors for the tenth-grade students’ reluctance to interact in the classroom during distance learning (An exploratory study from the point of view of students in the Sultanate of Oman) - Alkalbani, Said Mohammed (Journal of Educational and Psychological Sciences, 2023)
The study aimed to reveal the factors of tenth grade students’ reluctance to interact during distance education from the students’ point of view. The researcher used the qualitative approach, and the study sample consisted of (32) male and female students who were randomly selected from the schools of North Al Batinah Governorate in Oman. distributed into (4) focus groups. The focus group interview was used as a research tool. The reliability and validity of the tool were verified by arbitration and applied to a pilot sample. Its results showed that the teacher’s style and his social, educational, and technical skills amounted to 93.7% of repetition among the sample, and 84.3% of teaching strategies and methods are considered direct factors for reluctance. It also revealed that the student’s educational environment and psychological factors are also factors that influence students’ reluctance to interact in class. The study recommended the establishment of a national program for preparing teachers and training teachers in line with distance education, and the need to develop curricula and assessment tools.